An investigation into the use of derivatives by the 3rd tier South African companies - Donaldson, Alasdair (Department of Finance and Tax, 2014)
This investigation focuses on the use of derivatives by third-tier South African companies. The market capitalisation of these companies ranges from R65 million to R600 million.